Introducing Natural Resource Economics: Basic Concepts and Relevance to Economic Development - Resty Etika Pulungan; Rini Mayang Sari; Yutia Anggraini (Penerbit Merdeka Kreasi, 2024)
Natural resources are an element of the environment that has important value in meeting human needs. Natural resource economics is concerned with the management, use, and conservation of resources, including renewable and non-renewable resources. According to experts, natural resources can be classified according to their materials, habitat, and recreational capabilities. It includes biological and abiotic resources, soil and water, renewable and non-renewable resources. Sustainable economic development requires careful use of natural resources, as overexploitation can damage the environment and affect the wellbeing of future generations. Despite sustainable management efforts, Indonesia still faces major challenges such as environmental damage, climate change, and social conflicts. Policies that pay attention to environmental sustainability allow Indonesia to maximize the economic benefits of its natural resources while maintaining ecological balance and community welfare.